2020
DOI: 10.1007/s40273-020-00895-6
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Economic Models Across the Entire Schizophrenia Pathway

Abstract: Background: Schizophrenia is associated with a high economic burden. Economic models can help to inform resource allocation decisions to maximise benefits to patients.Objectives: This systematic review aims to assess the availability, quality and consistency of conclusions of health economic models evaluating the cost-effectiveness of interventions for schizophrenia. Methods: An electronic search was performed on multiple databases (MEDLINE, EMBASE, PsycInfo, Cochrane database of systematic reviews, NHS Econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 85 publications
0
10
0
Order By: Relevance
“…Given the volume of literature reporting health economic models in all disease areas, it was not feasible to consider the value of applying model selection tools to all published health economic models. Instead, we used a convenience sample of health economic models taken from a systematic review we recently conducted of health economic models which assessed the cost-effectiveness of interventions for people with schizophrenia, including both pharmacological and non-pharmacological interventions [23]. Of the 64 health economic models identified by the systematic review, 53 models assessed antipsychotic medications and these were used as a case study to explore the use of model selection tools.…”
Section: Case Study -Assessing the Value Of Application Of Model Sele...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the volume of literature reporting health economic models in all disease areas, it was not feasible to consider the value of applying model selection tools to all published health economic models. Instead, we used a convenience sample of health economic models taken from a systematic review we recently conducted of health economic models which assessed the cost-effectiveness of interventions for people with schizophrenia, including both pharmacological and non-pharmacological interventions [23]. Of the 64 health economic models identified by the systematic review, 53 models assessed antipsychotic medications and these were used as a case study to explore the use of model selection tools.…”
Section: Case Study -Assessing the Value Of Application Of Model Sele...mentioning
confidence: 99%
“…Review of citations of the identified model selection tools found that the seven tools were only cited 126 times by model-based health economic evaluations. This number is very small, given the total number of health economic models that are developed, for instance, for a single disease there are 73 for schizophrenia [23] and over 100 for diabetes [49]. The most commonly cited tool was the Brennan's toolkit [2] (50.0%).…”
Section: Use Of Tools In Health Economic Modelsmentioning
confidence: 99%
“…1 A 2020 systematic review found several limitations of existing economic models for schizophrenia. 2 Most existing models (83%) focused on antipsychotic medications, while there was a lack of models for nonpharmacologic interventions, such as cognitive behavioral therapy (CBT), family intervention, and crisis resolution and home treatment team (CRHT). Second, no antipsychotic medication was shown to be clearly cost-effective compared with the others because of inconsistent or even contradictory conclusions reported by different studies.…”
Section: Introductionmentioning
confidence: 99%
“…If important impacts of an intervention are omitted, the model results will be flawed and resource allocation decisions may be incorrect [ 13 ], with potential consequences including wasted resources in the healthcare system and quality of life and survival losses in the population concerned. Several systematic reviews [ 7 , 14 18 ] have been conducted for economic evaluations of antipsychotic medications for people with schizophrenia, and they all reported inconsistency in conclusions reported by different models. However, none of the published systematic reviews explored and compared the key clinical and cost impacts of antipsychotic medications considered by existing models.…”
Section: Introductionmentioning
confidence: 99%